2020
DOI: 10.1039/d0me00051e
|View full text |Cite
|
Sign up to set email alerts
|

Placement of tyrosine residues as a design element for tuning the phase transition of elastin-peptide-containing conjugates: experiments and simulations

Abstract: This study uses simulations and experiments to explain why and how the placement of tyrosine residues in elastin-peptide containing conjugates impacts their transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 78 publications
2
33
0
Order By: Relevance
“…In the directional coarse-grained model, we embed additional directional interaction sites within each matrix bead and nanorod bead, as shown in Figure b. This directional interaction model is based on previous CG models used by Jayaraman and co-workers to study a variety of synthetic and biologically relevant polymers with directional interactions as well as previous patchy particle models (see references to these in this viewpoint). In this directional interaction model, each directional interacting site is a sphere of diameter 0.25 d placed 0.37 d from the center of its parent matrix bead of diameter 1 d or nanorod bead of diameter D .…”
Section: Methodsmentioning
confidence: 99%
“…In the directional coarse-grained model, we embed additional directional interaction sites within each matrix bead and nanorod bead, as shown in Figure b. This directional interaction model is based on previous CG models used by Jayaraman and co-workers to study a variety of synthetic and biologically relevant polymers with directional interactions as well as previous patchy particle models (see references to these in this viewpoint). In this directional interaction model, each directional interacting site is a sphere of diameter 0.25 d placed 0.37 d from the center of its parent matrix bead of diameter 1 d or nanorod bead of diameter D .…”
Section: Methodsmentioning
confidence: 99%
“…The role of aromatic AAs in the UCST- and LCST-type transition behaviors appears to have particular significance ( Martin and Mittag, 2018 ). The LCST of ELPs is affected mainly by hydrophobic interactions ( Pak et al, 2016 ; Ruff et al, 2018 ) but may also be affected by hydrogen bonding and π-π stacking of the aromatic side-chains ( Taylor et al, 2020 ). In contrast, several studies have demonstrated that the UCST transition appears to be strongly influenced by the fraction, position, and identity of aromatic AAs and their interactions with other AAs (e.g., cation-π interactions), as well as by the overall hydrophobicity ( Joseph et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…performed atomistic and coarse‐grained molecular dynamics (MD) simulations to predict the LCST‐like transition of ELP‐CLP conjugates. [ 109 ] They chose a series of short ELPs containing tyrosine and/or phenylalanine guest residues with only five or six pentapeptide repeat units and fused them to a (GPO) 8 GG CLP sequence. In addition to hydrophobic collapse and H‐bonding interactions which are considered to be the driving forces promoting ELP collapse, the computational studies indicated that π – π stacking interactions can also be crucial when designing ELPs and ELP‐CLP conjugates.…”
Section: Elastin‐like Polypeptidesmentioning
confidence: 99%